Passing through – reasons why migrant doctors in Ireland plan to stay, return home or migrate onwards to new destination countries. Issue 1 (June 2016) - Brugha, Ruairí; McAleese, Sara; Dicker, Pat; Tyrrell, Ella; Thomas, Steve; Normand, Charles; Humphries, Niamh
Abstract Background International recruitment is a common strategy used by high-income countries to meet their medical workforce needs. Ireland, despite training sufficient doctors to meet its internal demand, continues to be heavily dependent on foreign-trained doctors, many of whom may migrate onwards to new destination countries. A cross-sectional study was conducted to measure and analyse the factors associated with the migratory intentions of foreign doctors in Ireland. Methods A total of 366 non-European nationals registered as medical doctors in Ireland completed an online survey assessing their reasons for migrating to Ireland, their experiences whilst working and living in Ireland, and their future plans. Factors associated with future plans – whether to remain in Ireland, return home or migrate to a new destination country – were tested by bivariate and multivariate analyses, including discriminant analysis. Results Of the 345 foreign doctors who responded to the question regarding their future plans, 16 % of whom were Irish-trained, 30 % planned to remain in Ireland, 23 % planned to return home and 47 % to migrate onwards. Country of origin, personal and professional reasons for migrating, experiences of training and supervision, opportunities for career progression, type of employment contract, citizenship status, and satisfaction with life in Ireland were all factors statistically significantly associated with the three migratory outcomes. Conclusion Reported plans may not result in enacted emigration. However, the findings support a growing body of evidence highlighting dissatisfaction with current career opportunities, contributing to the emigration of Irish doctors and onward migration of foreign doctors. Implementation of the WHO Global Code, which requires member states to train and retain their own health workforce, could also help reduce onward migration of foreign doctors to new destination countries. Ireland has initiated the provision of tailored postgraduate training to doctors from Pakistan, enabling these doctors to return home with improved skills of benefit to the source country.